2019
DOI: 10.1007/s10237-019-01259-6
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar spinal ligament characteristics extracted from stepwise reduction experiments allow for preciser modeling than literature data

Abstract: Lumbar ligaments play a key role in stabilizing the spine, particularly assisting muscles at wide-range movements. Hence, valid ligament force-strain data are required to generate physiological model predictions. These data have been obtained by experiments on single ligaments or functional units throughout the literature. However, contrary to detailed spine geometries, gained, for instance, from CT data, ligament characteristics are often inattentively transferred to multi-body system (MBS) or finite element … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…In particular, the three degree of freedom joint neglects translations permitted by the intervertebral disc, ligaments, and facet joints. While it is possible to improve musculoskeletal models with ligaments (Damm et al, 2019 ) and a better intervertebral disc representation (Wang et al, 2020 ), future work will implement the ligaments, discs, and facet joints in a finite element model of multiple spinal units. This is expected to reduce the impact of idealised musculoskeletal joints on the vertebra of interest.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the three degree of freedom joint neglects translations permitted by the intervertebral disc, ligaments, and facet joints. While it is possible to improve musculoskeletal models with ligaments (Damm et al, 2019 ) and a better intervertebral disc representation (Wang et al, 2020 ), future work will implement the ligaments, discs, and facet joints in a finite element model of multiple spinal units. This is expected to reduce the impact of idealised musculoskeletal joints on the vertebra of interest.…”
Section: Discussionmentioning
confidence: 99%
“…All passive force-transmitting structures, i.e., intervertebral disks (IVD), ligaments and facet joints, were modeled as nonlinear spring-damper elements (Damm et al. 2019 ). Here, particularly force-length and force-angle characteristics of ligaments and IVD, respectively, were extracted from step-wise reduction experiments (Heuer et al.…”
Section: Model and Methodsmentioning
confidence: 99%
“…Ligament insertion points were set manually (Schünke et al 2015) and counter-checked by neurosurgeons from the university clinic in Mainz. All passive force-transmitting structures, i.e., intervertebral disks (IVD), ligaments and facet joints, were modeled as nonlinear spring-damper elements (Damm et al 2019). Here, particularly force-length and force-angle characteristics of ligaments and IVD, respectively, were extracted from step-wise reduction experiments (Heuer et al 2007) and validated using data on range of motion (Heuer et al 2007) as well as intradiscal pressure (Wilke et al 1996).…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…From the calibrated figure 7.14 in a most recent source (Williams and Meyer, 2017), the dimensions of an Australopithecus afarensis L4 endplate can be read off: a width of Accordingly, properly determining endplate areas, just like muscle and ligament lever arms, in extant species or from fossil records are all key to well predicting compressive IVD stresses. As a last example, referring to material properties, it has recently been shown that widely scattering published data on spinal ligament properties, their stiffnesses (Mörl et al, 2020;Damm et al, 2019) and rest lengths (Mörl et al, 2020) in particular, are a source of erroneous calculations of loads on all spinal structures. Consequently, our second major conclusion is that the mechanical function(s) of an anatomical structure, as well as functional interrelations between structures, are desirable to always be kept in mind when experimentally examining and determining anatomical and material properties.…”
Section:  mentioning
confidence: 99%